2022
DOI: 10.1155/2022/8970549
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Meat and Poultry Farm Inventory Stock Using Data Analytics for Green Supply Chain Network

Abstract: The traditional meat and poultry farms use a fixed quantity of supply, which creates an imbalance between demand and supply. Due to this imbalance, a huge amount is spent on balancing the requirements. There is an inequality among demand and supply since typical meat and poultry farms use a fixed amount of supply. A lot of money is spent trying to balance the requirements because of this mismatch. In addition, when connecting and building the meat and poultry farm system, the procedure ignores the impact on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…While data analytics may significantly improve process efficiency and optimization in the meat processing business, it is crucial to prioritize data security and control. Processors must follow industry standards and data protection laws and put strong cybersecurity measures in place to guard sensitive data from tampering or illegal access [30].…”
Section: Data Analytics For Process Optimizationmentioning
confidence: 99%
“…While data analytics may significantly improve process efficiency and optimization in the meat processing business, it is crucial to prioritize data security and control. Processors must follow industry standards and data protection laws and put strong cybersecurity measures in place to guard sensitive data from tampering or illegal access [30].…”
Section: Data Analytics For Process Optimizationmentioning
confidence: 99%
“…When planning the development of poultry processing enterprises, it is necessary to consider the impact of their functioning on the environment. R. Kler et al (2022) found that during the production of high-quality and safe meat of broiler chickens, it is necessary to ensure proper sanitary and hygienic conditions for their maintenance, feeding, and well-being. S. Tavaniello et al (2023) proved a significant effect of the synbiotic drug "PoultryStar", when fed to broiler chickens, on increasing body weight, carcass yield, improving the quality indicators of meat and offal, in particular morphological ones.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable development has received widespread attention from various industries [1][2][3]. With the increase in the throughput of container terminals worldwide, maritime transport for trade and development has become increasingly important [4].…”
Section: Introductionmentioning
confidence: 99%